The great pretender : the undercover mission that changed our understanding of madness - Cahalan, Susannah (Grand Central Publishing, 2019)
For centuries, doctors have struggled to define mental illness--how do you diagnose it, how do you treat it, how do you even know what it is? In search of an answer, in the 1970s a Stanford psychologist named David Rosenhan and seven other people--sane, normal, well-adjusted members of society--went undercover into asylums around America to test the legitimacy of psychiatry's labels. Forced to remain inside until they'd "proven" themselves sane, all eight emerged with alarming diagnoses and even more troubling stories of their treatment. Rosenhan's watershed study broke open the field of psychiatry, closing down institutions and changing mental health diagnosis forever. But, as Cahalan's explosive new research shows, very little in this saga is exactly as it seems. What really happened behind those closed asylum doors, and what does it mean for our understanding of mental illness today?